ChemInform Abstract: Palladium‐Catalyzed C(sp2)—H Alkylation of Aldehyde‐Derived Hydrazones with Functionalized Difluoromethyl Bromides. Issue 23 (May 2016) - Prieto, Alexis; Melot, Romain; Bouyssi, Didier; Monteiro, Nuno
Abstract: The Pd‐catalyzed difluoromethylation of aldehyde‐derived hydrazones using bromodifluoromethylated compounds affords functionalized difluoromethylketone hydrazones.